Pelatihan Pengelolaan Keuangan dan Manajemen Produksi Karet pada Petani Karet di Pulau Harapan - Silvana Oktanisa; Rosita Rosita; Yusleli Herawati; Meli Septiani; Rizky R.C.; Astri Febria; Stenia R. Y. (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This training was held in Pulau Harapan Village. Pulau Harapan Village is a village that has potential in rubber plantations. Most of its people live from rubber farming. In terms of income, people usually get paid from rubber farming once a week. People tend to find it difficult to manage their finances, which they think they only get a little from rubber farming and most of them only work as rubber farmers without any other jobs that produce income. In addition, rubber production is also not very good because most rubber farmers themselves do not understand the science of rubber production management. The purpose of implementing this community service activity is to provide knowledge to rubber farmers about financial management and rubber production management. The training was held for one day. From this training, it was discovered about the obstacles in the training, the results of the training obtained from the discussion and pre-test and post-test stated that rubber farmers had begun to understand about managing finances and understanding rubber production management. The results of this community service can be used as an initial step for further assistance to rubber farmer groups in Pulau Harapan Village.